Socialization and Training on the Use of E-learning for Teachers at the Advent Education Foundation in Sausapor District - Setyawan, Muhammad Rizki; Kahar, Muhammad Syahrul; Sangadji, Zulkarnain; Febriadi, Ihsan; Aronggear, Karim Paul (Universitas Lambung Mangkurat, 2025)
Through socialization and training, this community service activity aimed to enhance teachers' competencies in utilizing e-learning platforms at the Advent Education Foundation in the Sausapor District. The initiative responded to challenges in adopting digital technology, minimal technological infrastructure, and teachers' lack of proficiency in digital tools, further exacerbated by the COVID-19 pandemic. The activity aligned with the Merdeka Belajar Curriculum, which emphasizes flexibility and personalization in learning. We employed a participatory action research (PAR) method, engaging participants directly in the training process. The stages of the activity included planning, preparation, execution, and reporting. Results indicated a high level of enthusiasm among teachers, with many demonstrating an improved understanding of key e-learning tools and their integration into the Merdeka Belajar Curriculum. However, challenges remain, particularly in technological infrastructure and teachers' adaptation to online learning formats. Despite these obstacles, this activity successfully enhanced teachers' knowledge and skills about e-learning. Recommendations for continuous training and establishing internal working groups are proposed to support the effective and sustainable implementation of e-learning in the Sausapor District. This initiative highlights the importance of targeted efforts to improve digital competencies in education, particularly in remote areas.